2021
DOI: 10.1080/00918369.2021.1948771
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Lesbians, Gay Men, and Their Rights in a Sample of Ecuadorian Cisgender Men and Women

Abstract: Since 1997, Ecuador has undergone a series of changes to ensure family rights to sexual minorities. However, there is still limited research regarding attitudes toward them. This study focused on the attitudes toward lesbians (L), gay men (G), and their rights. A sample of 318 cisgender Ecuadorians who responded to an online survey was recruited. Analyses indicated that men, heterosexuals, who practice their religion, attend more frequently to religious services, and identify as conservative showed higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
7
3
0
2
Order By: Relevance
“…In line with previous studies (Detenber et al, 2013;Song et al, 2014;Liu, 2020;Hermosa-Bosano et al, 2021), our findings have suggested that exposure to homosexual content or having prior contact with homosexuals might contribute to greater tolerance of homosexuals. Given the fact that less than half of them were exposed to homosexual content or had a homosexual friend, undergraduates should be recommended to read materials depicting homosexuality in a positive way (e.g., explaining that homosexuality is the same as heterosexuality and is also a normal sexual orientation) or increase positive encounters with LG (Altemeyer, 2002;Salvati et al, 2019) such as inviting some volunteers to share their personal stories (Eick et al, 2016) to dispel myths, reduce fear, promote mutual understanding and finally reduce prejudice toward homosexual individuals.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous studies (Detenber et al, 2013;Song et al, 2014;Liu, 2020;Hermosa-Bosano et al, 2021), our findings have suggested that exposure to homosexual content or having prior contact with homosexuals might contribute to greater tolerance of homosexuals. Given the fact that less than half of them were exposed to homosexual content or had a homosexual friend, undergraduates should be recommended to read materials depicting homosexuality in a positive way (e.g., explaining that homosexuality is the same as heterosexuality and is also a normal sexual orientation) or increase positive encounters with LG (Altemeyer, 2002;Salvati et al, 2019) such as inviting some volunteers to share their personal stories (Eick et al, 2016) to dispel myths, reduce fear, promote mutual understanding and finally reduce prejudice toward homosexual individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (Herek and Gonzalez-Rivera, 2006;Yu et al, 2011;Liu and Sun, 2015;Zhang et al, 2016;Liu, 2020;Hermosa-Bosano et al, 2021), men were more likely than women to express negative attitudes toward LG (in particular homosexuals of the same gender, i.e., gay men). This finding can be explained by the fact that machismo culture still prevails in mainland China.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations